2021
DOI: 10.1002/sstr.202100067
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of 2D Nanosheets into 1D Nanostructures for Sensing NO2

Abstract: Ultrathin 2D nanosheets are one of the appealing building blocks for constructing self‐assembled nanostructures. Herein, a facile, fast, and general solvent‐mediated route for the high‐yield and large‐scale self‐assembly of ultrathin 2D nanosheets into 1D nanofibers and nanorings is reported. Solution‐dispersed graphene oxide (GO), MoS2, TiS2, and TaS2 nanofibers with lengths of several tens of micrometers and diameters of 20–50 nm are formed via the self‐assembly of their corresponding single‐layer nanosheets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…S7 in the ESI†), which enabled facile electron transfer across the Au/α-Fe 2 O 3 interface, leading to the formation of additional electron vacancies in α-Fe 2 O 3 and thus an enhanced sensitivity. In addition, our Au ND–ODT/α-Fe 2 O 3 /rGO-based sensor exhibits performance comparable to that of many previously reported RT NO 2 gas sensors (see Table S1 in the ESI†) 53–61 and outperforms the recently reported rGO nanofiber, 54 Au–CuO 59 and MoS 2 (ref. 60) based sensors.…”
Section: Resultssupporting
confidence: 82%
“…S7 in the ESI†), which enabled facile electron transfer across the Au/α-Fe 2 O 3 interface, leading to the formation of additional electron vacancies in α-Fe 2 O 3 and thus an enhanced sensitivity. In addition, our Au ND–ODT/α-Fe 2 O 3 /rGO-based sensor exhibits performance comparable to that of many previously reported RT NO 2 gas sensors (see Table S1 in the ESI†) 53–61 and outperforms the recently reported rGO nanofiber, 54 Au–CuO 59 and MoS 2 (ref. 60) based sensors.…”
Section: Resultssupporting
confidence: 82%
“…[25][26][27] Additionally, previous studies have shown that graphene and graphene-like two-dimensional nanosheets can curl spontaneously to form nanoscroll-structured materials with excellent physicochemical properties for applications in sensors, electronics, energy storage, electrocatalysis, etc. [28][29][30][31][32][33][34][35][36] Motivated by these observations, it would also be interesting to figure out whether metallic WSe 2 (M-WSe 2 ) nanosheets can also form the nanoscrolls via a spontaneous curling process. However, it is still quite challenging to construct metastable metallic phase TMD nanomaterials owing to their thermodynamic metastable nature.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of 2D nanosheet into basic material could supply good sensitivity since 2D nanomaterials are used as the channel material to fabricate sensor. 50 Therefore by combining Ti 3 C 2 T x with high conductivity and Cu-BTC, the conductivity of Cu-BTC can be greatly improved, the response current and current change value can be increased, and the sensing signal can be significantly amplified.…”
Section: Resultsmentioning
confidence: 99%